VIDEOGAMES AND EDUCATION UNDER A CIBERCULTURAL VIEW (Fiep Bulletin - online, 2013)
Electronic games, especially those played in LAN Houses, became a real fever in urban areas of Brazil. Aiming to investigate the possibilities of correlation between games and the media, proposing the conversion / transfer of the virtual game in a possible educational experience, a systematic review of qualitative research was developed. The analytical scheme went through the identification and description of the terms: Electronics Games, Education, Virtual, Cyberculture and Videogames, with the help of the digital Databases of BIREME. With the technological innovations in information and communication come new forms of socialization, and consequently a new form of culture: cyberculture, in which new knowledge grows before a new social setting, where the consumption of information and images from the media presents itself as creator of contemporary culture. It follows that with the advent of new technologies, an increasingly virtual space is created, a cyberspace which generates new and interesting forms of learning.
Keywords: Electronic Games; Education; Cyberculture